Determinants of Company Value in the Health Sector in 2020-2023 - Susilawati; Yuniarwati (Politeknik Negeri Madiun, 2025)
Financial performance, audit opinion, and audit quality of a company can provide information about the condition of the company. The fairness status of financial statements can reveal audit opinions, competent auditors can measure audit quality, and fundamental analysis can reveal financial performance. The purpose of this study is to determine how organizational value is affected by audit quality, audit opinion, and financial performance. Participants in this study were healthcare companies listed on the Indonesia Stock Exchange between 2020-2023. One of the research sample selection techniques is purposive sampling. Eighteen companies have met the research sample criteria. This study uses a descriptive method to analyze secondary data and multiple linear regression testing with conventional assumptions, t-tests, and f-tests. The findings show that, between 2020-2023, the value of healthcare companies listed on the Indonesia Stock Exchange is significantly positively affected by ROA and DAR, but not by audit opinions, and audit quality.